2013
DOI: 10.1161/atvbaha.112.300893
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-5 Controls Intercellular Barriers of Human Dermal Microvascular but Not Human Umbilical Vein Endothelial Cells

Abstract: Objective To assess the role claudin-5, an endothelial cell (EC) tight junction (TJ) protein, plays in establishing basal permeability levels in humans by comparing claudin-5 expression levels in situ and analyzing junctional organization and function in two widely used models of cultured ECs, namely human dermal microvascular (HDM)ECs and human umbilical vein (HUV)ECs. Methods and Results By immunofluorescence microscopy, ECs more highly express claudin-5 (but equivalently express VE-cadherin) in human derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 72 publications
6
81
0
Order By: Relevance
“…The proposed mechanisms for PKD-mediated permeability in human umbilical vein endothelial cell monolayers are different from ours in airway epithelial cells. A recent study has demonstrated that claudin-5 and tight junctions control paracellular permeability in arteriolar and capillary endothelial cell monolayers, whereas human umbilical vein endothelial cell and venular junctions use adherent junctional protein VE-cadherin for regulating barrier function (57). Moreover, in retinal microvascular endothelial cells, VEGF disturbs the barrier of the endothelial cell monolayers by inducing down-regulation of claudin-1 but not claudin-3, claudin-5, ZO-1, and VE-cadherin (58).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms for PKD-mediated permeability in human umbilical vein endothelial cell monolayers are different from ours in airway epithelial cells. A recent study has demonstrated that claudin-5 and tight junctions control paracellular permeability in arteriolar and capillary endothelial cell monolayers, whereas human umbilical vein endothelial cell and venular junctions use adherent junctional protein VE-cadherin for regulating barrier function (57). Moreover, in retinal microvascular endothelial cells, VEGF disturbs the barrier of the endothelial cell monolayers by inducing down-regulation of claudin-1 but not claudin-3, claudin-5, ZO-1, and VE-cadherin (58).…”
Section: Discussionmentioning
confidence: 99%
“…Six genes related to endothelial cells and angiogenesis also belonged to this top list. These genes encoded for proteins regulating at different levels the endothelial/vascular permeability (26)(27)(28) and differentiation of endothelial cells (29) and included both transcription factors and adhesion molecules. Moreover, VEGF-related genes, such as the gene encoding for VEGFR3 or enzyme affecting HIF1 and VEGF expression, resulted also upregulated in IM-treated tumors (Table 4; ref.…”
Section: Whole Transcriptome Sequencingmentioning
confidence: 99%
“…ECs from different types of vessels and also from different organs show differences in junction composition and organization Kluger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%